The Power of Sequence: A Qualitative Analysis of Consumer Targeting and Spillover Effects in Social Media Advertising - Eka Wahyu Kasih; Benardi Benardi; Ruslaini Ruslaini (LPPM STIE Kasih Bangsa, 2024)
This qualitative literature review titled